2017
DOI: 10.3390/ma10030290
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Quasi-Static Indentation Response of Inkjet Printed Sandwich Structures under Various Indenter Geometries

Abstract: The objective of this investigation was to determine the quasi-static indentation response and failure mode in three-dimensional (3D) printed trapezoidal core structures, and to characterize the energy absorbed by the structures. In this work, the trapezoidal sandwich structure was designed in the following two ways. Firstly, the trapezoidal core along with its facesheet was 3D printed as a single element comprising a single material for both core and facesheet (type A); Secondly, the trapezoidal core along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Inkjet printing had been explored to fabricate variety of sandwich structures with different complex core designs and facesheet configurations. For example, core designs that include trapezoidal vertical pillared [18], sinusoidal vertical pillared [8], and special honeycombs [19] have been printed. Inkjet printed structures have shown shape recovery effects and better energy-absorption characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inkjet printing had been explored to fabricate variety of sandwich structures with different complex core designs and facesheet configurations. For example, core designs that include trapezoidal vertical pillared [18], sinusoidal vertical pillared [8], and special honeycombs [19] have been printed. Inkjet printed structures have shown shape recovery effects and better energy-absorption characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the work to be presented in this paper is a continuation of the work done on multimaterial sandwich structures previously manufactured using Inkjet printing technique [8,18]. The quasi-static indentation (QI) properties of trapezoidal vertical pillared (core-1) and sinusoidal vertical pillared (core-2) structures are investigated under various indenter (hemispherical, conical, and flat) geometries along with AE monitoring, and the results are discussed in the articles [8,18]. Moreover, a hypothesis of the damage mechanism in sinusoidal vertical pillared structure was explained in [18], but no verification was provided regarding the proposed damage mechanism as the studies were limited to analyzing the damage using high-speed camera.…”
Section: Introductionmentioning
confidence: 99%
“…1c) with dimensions of 20x20x20 mm. The shape and dimensions of the tested specimens are important in determining mechanical properties while strength tests (Dikshit et al, 2017). Among many models, a cube was chosen as representing the simplest geometry, shortening time and facilitating the measurement and interpretation of results regarding geometric accuracy.…”
Section: Tested Specimensmentioning
confidence: 99%
“…It was found that AE signals can distinguish three basic failure modes such as matrix cracking, delamination and fiber breaking. In addition, Dikshit et al 14 presented AE technology to determine the quasi-static indentation response and failure modes in three-dimensional (3D) printed trapezoidal core structures. It was indicated that the major failure modes were quasi-brittle fractures under indentation.…”
Section: Introductionmentioning
confidence: 99%